2008
DOI: 10.4314/ajhs.v14i3.30862
|View full text |Cite
|
Sign up to set email alerts
|

A study of the pharmaceutical quality of chloroquine and paracetamol products sold in a major Nigerian “market”

Abstract: SUMMARYMalaria is a major public health problem in endemic countries, and the quality of antimalarial products is a concern in the therapeutic management of individual patient. In this study, we have evaluated the pharmaceutical quality of chloroquine and paracetamol oral products obtained from a major Nigerian drug "market" using a less elaborate sampling procedure. Results have shown that there are still some defects in the pharmaceutical quality of these drugs, despite the activities of the Nigeria's drug r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Previous studies in Southeast Nigeria and Sudan revealed that the poor-quality drugs are highly distributed and circulating intensively in the market (Alfadl et al, 2006;Onwujekwe et al, 2009). However, availability of substandard drugs is the most important challenge to the chemotherapy of malaria and other infectious diseases in the developing communities (Ofonaike et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in Southeast Nigeria and Sudan revealed that the poor-quality drugs are highly distributed and circulating intensively in the market (Alfadl et al, 2006;Onwujekwe et al, 2009). However, availability of substandard drugs is the most important challenge to the chemotherapy of malaria and other infectious diseases in the developing communities (Ofonaike et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Africa focused studies that intended to investigate the quality of chloroquine tablets found in African countries showed that percentage failures in dissolution ranged from 5% to 50%, in ingredient content from 20% to 67%, in disintegration was 20%, in crushing strength was 30%, and friability test was 21%. [19][20][21] Another commonly prescribed drug for malaria in Ethiopia is quinine. Quinine contains in its structure a quinoline nucleus and an amino alcohol side chain.…”
Section: Introductionmentioning
confidence: 99%
“…One of the expected consequences of treatment failure in AN is a longer duration of malaria morbidity because, by adult age, herd immunity is usually well established and mortality is extremely rare ( Gavazzi et al, 2004 ). Other considerations that may guide decision is that while ACT has high rates of substandard preparations that contain between 74%and 77% ( Atemnkeng et al, 2007 , Raufu, 2002 ) of the value stated by the manufacturer and currently have treatment failures of about 1–18% ( Ittarat et al, 2003 ; Ajayi et al, 2008a ), CQ has substandard preparations that contain 0–87% ( Ofonaike et al, 2007 ) but those that contain above 50% (89% of substandard CQ) of the label value are still efficacious in non-resistant parasite because CQ concentrates within parasite vacuoles ( Shapiro and Goldberg, 2001 ). Two different strategies may therefore be considered to be available as potential first line treatments in adults with uncomplicated malaria namely-ACT or CQ plus ACT when needed (CQ plus as needed Artemisinin combination treatment-CANACT).…”
Section: Introductionmentioning
confidence: 99%